High Rates of Non-Response Across Treatment Attempts in Chronic Irritable Bowel Syndrome: Results From a Follow-Up Study in Tertiary Care - Dong, Yuanjun; Baumeister, David; Berens, Sabrina; Eich, Wolfgang; Tesarz, Jonas (Frontiers in Psychiatry, 2019)
Objective: Despite a wealth of treatment options of irritable bowel syndrome (IBS), data on the subjective experience of treatments in ongoing clinical practice are sparse. This follow-up study assessed the individual usage of treatment modalities by IBS patients over time and investigated the patients’ subjective experience of therapeutic impact. Methods: The study was conducted at a specialty clinic for Functional Gastrointestinal Disorders of the Heidelberg University Hospital. All patients who fulfilled the Rome III criteria for IBS and treated in our outpatient clinic between January 2012 and December 2016 were invited to the assessment. The primary outcome variables were individual usage of treatment modalities and the patients’ global impression of change (PGIC) with treatments. Results: 366 patients fulfilled the Rome III criteria for IBS and thus were eligible for this study. 207 patients dropped out in the study. The study could include 159 patients (43.7±17.1 years; 71.1% female). The mean time since the first visit to the clinic was 2.8±1.3 years (median 3.0 years). The mean time of symptom duration was 14.1±11.1 years (median 10 years). The average number of treatment attempts was 12, ranging from 2 to 39). With respect to the subjective experience of therapeutic impact, there were no significant differences with the PGIC scores among different treatments (p=0.183). The rates of non-response rates (minimally improved, no change, or minimally worse) ranged from 63.0% to 83.9%. The PGIC score was correlated negatively with the mean number of treatment attempts (r=-0.316, p<0.01). The mean number of treatment attempts was correlated negatively with quality of life (r=-0.262, p<0.01). Conclusion: Multidisciplinary treatment approach of IBS is characterized by high rates of non-response and a high number of frustrating treatment attempts. The connection between the various treatment attempts and the frustrating subjective experience of therapeutic impact puts a substantial burden on IBS patients.